Flavonoids Inhibit the Respiratory Burst of Neutrophils in Mammals. (23rd April 2012) - Ciz, Milan; Denev, Petko; Kratchanova, Maria; Vasicek, Ondrej; Ambrozova, Gabriela; Lojek, Antonin
Abstract : Neutrophils represent the front-line defence cells in protecting organisms against infection and play an irreplaceable role in the proper performance of the immune system. As early as within the first minutes of stimulation, neutrophilic NADPH oxidase is activated, and cells release large quantities of highly toxic reactive oxygen species (ROS). These oxidants can be highly toxic not only for infectious agents but also for neighboring host tissues. Since flavonoids exhibit antioxidant and anti-inflammatory effects, they are subjects of interest for pharmacological modulation of ROS production. The present paper summarizes contemporary knowledge on the effects of various flavonoids on the respiratory burst of mammalian neutrophils. It can be summarized that the inhibitory effects of flavonoids on the respiratory burst of phagocytes are mediated via inhibition of enzymes involved in cell signaling as well as via modulation of redox status. However, the effects of flavonoids are even more complex, and several sites of action, depending upon the flavonoid structure and way of application, are included.